Mapping Hoax Themes During The Early PPKM Darurat Policy in Indonesia - Lelita Azaria Rahmadiva; Bono Setyo; Siantari Rihartono (Communications, 2024)
The development of information and communication technology has indeed provided convenience in handling Covid-19. On the other hand, this condition has an unexpected impact, namely the infodemic. The infodemic phenomenon is caused by exposure of a large amount of information that allows true and false information to be accessed. It becomes a problem when these hoaxes become a reference for the public in handling COVID-19. This research aims to map the hoax themes that most frequently emerged during the emergency PPRM period, and analyze the causes of hoaxes circulating massively during the pandemic. This study will further discuss hoax themes during the early PPKM Darurat Covid-19 Outbreak Policy from 1st - 12th July 2021. The online qualitative approach is used as a tool to view and analyze this phenomenon. The hoaxes analyzed came from Cekfakta.com which is a hoax verification portal in Indonesia. Hoaxes that were informed on the portal were then collected and analyzed for themes, sources. The results of this research show that social media becomes the main source of hoax circulation. There are three major theme trends that become hoaxes in the early PPKM Darurat in Indonesia, namely politics, health, and religion. There are three things that affect the masiv spread of hoaxes, namely: 1) Community culture, 2) The development of digital technology, 3) Low media literacy. Two recommendations that can be given through this research are digital literacy in society, and the development of tabayyun, namely checking and rechecking information before it is received and distributed.